Case report: Histoplasmosis presenting as asymptomatic hypercalcemia detected on routine laboratory testing in a pediatric kidney transplant recipient - Spiwak, Elizabeth; Goswami, Shrea; Lay, Sara E.; Nailescu, Corina (Frontiers in Pediatrics, 2023)
Amongst all infections occurring in pediatric kidney transplant recipients, approximately 1-5% are fungal in origin. Most fungal infections occur in the first six months following kidney transplantation. We present the case of a 15-year-old male with history of a kidney transplant four years prior, who was found to have asymptomatic moderate hypercalcemia on routine laboratory testing, along with an acute deterioration of his kidney function markers. The cause of his acute kidney injury was likely related to the hypercalcemia. An extensive workup for hypercalcemia revealed an infection with Histoplasma capsulatum (histoplasmosis) with multiple pulmonary nodules. Hypercalcemia that was initially refractory to medical management resolved after initiating the antifungal treatment. Fungal granulomatous infections such as histoplasmosis should be considered in the differential diagnosis of hypercalcemia in an asymptomatic pediatric kidney transplant recipient.